If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 2y = 15 + -3y Solving 5 + 2y = 15 + -3y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '3y' to each side of the equation. 5 + 2y + 3y = 15 + -3y + 3y Combine like terms: 2y + 3y = 5y 5 + 5y = 15 + -3y + 3y Combine like terms: -3y + 3y = 0 5 + 5y = 15 + 0 5 + 5y = 15 Add '-5' to each side of the equation. 5 + -5 + 5y = 15 + -5 Combine like terms: 5 + -5 = 0 0 + 5y = 15 + -5 5y = 15 + -5 Combine like terms: 15 + -5 = 10 5y = 10 Divide each side by '5'. y = 2 Simplifying y = 2
| G=9/4(p-1) | | 30=5c+20 | | 15-27b+11=-244 | | 46+X=349 | | 5x-1=2x-5 | | LOG(7)(4-X)=1 | | 3x-14+3x=3+6x-17 | | 15a^2-6ab-8a^2+20-5ab-31+a^2-ab=0 | | LOG(7)4-X=1 | | 10x=9x+21 | | 9y^2+24y+72x+16=0 | | (.2x)+x=40 | | 45x=64x+8 | | 90=2w+2(2w+6) | | 11x=247 | | 5d+10=8d-14 | | (2x-5)(x)=52 | | 9=4y-y | | 7(2y-3)=2(4y-10) | | 30g+4=70 | | r^-3/r^-6 | | 77=x+x+2 | | (X-23)*x=0 | | w-8=7.6 | | 2(x-1)-5(3x-3)= | | (-3)x^2=45 | | 5(20+-4.4b+-1.4s)+7s+22b=100 | | 5a+7s+22b=100 | | x^4=200 | | x^4=217 | | X^4=347 | | 9/(x-3)=3x/(x-3) |